2020
DOI: 10.2337/db20-0057
|View full text |Cite
|
Sign up to set email alerts
|

Translational Factor eIF4G1 Regulates Glucose Homeostasis and Pancreatic β-Cell Function

Abstract: Protein translation is essential for cell physiology, and dysregulation of this process has been linked to aging-related diseases such as type 2 diabetes. Reduced protein level of a requisite scaffolding protein of the initiation complex, eIF4G1, downstream of nutrients and insulin signaling is associated with diabetes in humans and mice. In the current study, we tested the hypothesis that eIF4G1 is critical for β-cell function and glucose homeostasis by genetically ablating eIF4G1 specifically in β-cells in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Glucose and insulin tolerance tests were performed by intraperitoneal delivery of 2 g/kg glucose or 0.75 U/kg insulin (Novolin, Novo Nordisk Inc) to mice after 12 or 6 hours of fasting as previously described ( 57 ). The HOMA-IR index was calculated as (fasting insulin [ng/mL] × fasting glucose [mmol/L])/22.5 to assess insulin resistance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose and insulin tolerance tests were performed by intraperitoneal delivery of 2 g/kg glucose or 0.75 U/kg insulin (Novolin, Novo Nordisk Inc) to mice after 12 or 6 hours of fasting as previously described ( 57 ). The HOMA-IR index was calculated as (fasting insulin [ng/mL] × fasting glucose [mmol/L])/22.5 to assess insulin resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose and insulin tolerance tests were performed by intraperitoneal delivery of 2 g/kg glucose or 0.75 Unit/kg insulin (Novolin, Novo Nordisk Inc.) to mice after 12 or 6 hours of fasting as previously described (57).…”
Section: Metabolic Phenotypingmentioning
confidence: 99%
“…found that the mammalian rapamycin complex 1 (mTORC1) trophic sensing pathway is dysregulated in diabetes [ 110 ], while Seokwon Jo et al. demonstrated that the translation factor EIF-4G1 and EIF-4E protein damaged insulin secretion, glucose homeostasis and β-cell function in EIF-4G1 knockout [ 111 ]. This suggests the potential of EIF-4E and EIF-4G1 targeting therapies in reducing the risk of type 2.…”
Section: Rbps Implicated In the Development Of Multiple Diabetic Comp...mentioning
confidence: 99%
“…In βOGAKO islets, pro-insulin levels and pro-insulin to insulin ratio was reduced, and this is associated with increased expression of prohormone processing enzyme carboxypeptidase E (CPE), suggesting increased pro-insulin processing with possible reduction in pro-insulin transcription or translation. In our previous work in βOGTKO islets, a model of hypo-O-GlcNAcylation, we found that reduced insulin content occurred in part due to disruption in insulin transcription (decrease Ins1/2 mRNA and Pdx1 protein) as well as proinsulin processing, through dysregulation of CPE via O-GlcNAcylation of eIF4G1 ( 26 ). These data suggest that insulin processing in part through CPE and eIF4G1 is dependent on the presence of O-GlcNAcylation, where absence leads to reduced processing, while an increase in this PTM leads to enhanced proinsulin processing.…”
Section: Discussionmentioning
confidence: 99%